Disaster Porn!. (May 2013) - Recuber, Timothy
The term disaster porn has evolved over time, from an epithet directed at extreme depictions of suffering in the developing world, to a broader critique today of all sorts of disaster-related media—even fictional Hollywood blockbusters. Sociologist Timothy Recuber examines how disaster porn, in all its iterations and for all its flaws, is a vital political terrain in which publics are at least implicitly asked to struggle with the social significance of the suffering of others.